THE IMMORTAL DIVINE SPIRIT IN ALL THINGS (WIS 11:21-12:2) AGAINST ‘TYRANNICAL ANTHROPOCENTRICISM’ (LAUDATO SÍ, 68) - Obijiaku, Cletus U. (Asian Horizons, 2015)
Disproportionate emission of greenhouse gases has impacted very negatively on humans, animals and the entire environment. Humans perpetuate environmental degradation through their actions; and terminal ailments have become commonplace. Some environmentalists fault the anthropology of the Judeo-Christian Scripture or religion, accusing it of tyrannical anthropocentricism, which encourages humans to exploit the environment all the more. Pope Francis, in his Encyclical Laudato Sí, has rightly pointed out that this is a wrong interpretation of the Bible. He has rather called all humans to work together to protect the dignity of all creatures. This study has affirmed the Pope’s assertion through an in-depth exegetical study of Wis 11:21-12:2, a text that asserts the “immortal divine spirit” in all things. Every created thing has its immortal form in the divine mind that created it for a specific purpose. The form remains even when human beings can no longer see the matter. This study establishes a strong footing for authentic environmental theology. Consequently humans should not abuse any creature. Practical things that individuals could do daily to care for the environment are discussed.